PENGGUNAAN ASESMEN BERBASIS PORTOFOLIO UNTUK MENINGKATKAN KEAKTIFAN SISWA DALAM PROSES PEMBELAJARAN IPS DI SEKOLAH DASAR - Poerwanti, Jenny Indrastoeti Siti; Mahfud, Hasan (Jurnal Inovasi Pendidikan, 2010)
Related to the teaching and learning of IPS, the aim of this classroom action research is to improve: (1) the students' activities; (2) the students' motivation; and (3) the students' achievement. This research uses a spiral self-reflection model which consists of four steps: planning, action, observation, and reflection with two cycles. The research subject is the 38 students and the teacher of SD Negeri Tegalmulyo Kecamatan Laweyan Surakarta. The object is IPS subject matter taught in the Elementary School. The data were collected from result of writing test. The data are analyzed by using quantitative analysis. The results show that there is improvement of the students' mean scores from cycle 1 to cycle 2, based on the following aspects: (1) 36 % improvement on activities; (2) 17 % improvement on motivation; and (3) 12.3 % improvement on achievement.